America's "Greater Middle East" and Europe: Key issues for the transatlantic dialogue - Volker Perthes (Stiftung Wissenschaft und Politik (SWP), 2004)
Within the next few years, if not over the next few decades, the Middle East will become the focus of international geopolitics and thereby largely determine relations between Europe and America. The US administration has embraced the cause of bringing a 'new order' to the region and has underscored this by announcing a 'Greater Middle East Initiative' (GMEI), for which it will seek transatlantic approval at the forthcoming June 2004 NATO and G8 summits. (SWP Comments / SWP)
Keywords: 320